Juridical Review of The Crime of Attacking The President's And Vice-President's Honest And Dignity In The 2023 KUHP - Kartina Pakpahan; Elvira Fitriyani Pakpahan; Guntur Hutagalung (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The article's regulation in the Bill of the Criminal Code regarding acts of attacking the honor and dignity of the president has been criticized. Some articles are considered to have the potential to threaten the right to freedom of expression and freedom of the press, which are part of the human rights guaranteed by the Constitution. On the other hand, legislators also have a raison d’etre as the urgency of regulation. This study aims to explore in depth the significance of the substantial regulation of the articles, as well as to examine some potential conflicts with the right to freedom of expression and freedom of the press. This study is a type of normative legal research, with data analysis methods carried out with a qualitative approach to secondary data. The results of the analysis show that the articles concerning acts attacking the honor and dignity of the president or vice president still needed/urgent to be re-formulate in the Bill of the Criminal Code. However, it should be noted that it is necessary to adjust some of the explanations of the articles. In addition, the general construction of these articles cannot be said to have violated human rights principles related to the right to freedom of expression and freedom of the press. However, there should be an assurance that protecting the freedom of expression and freedom of the press still needs to be emphasized in the Bill of the Criminal Code. So far, the reality shows that there are still poor implementations in law enforcement related to some articles, such as articles on contempt.